The Effect Of Implementing The Story Map Technique On Students In Writing Ability Narrative Text - Himatul Fadhila (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
This research aimed to find out whether there was any significant effect of using Story Map technique on students’ English writing ability. The design was quasi experiment. The sample consisted of 58 students from the state institute of Islamic studies of Bengkulu, Indonesia. Descriptive and inferential statistics were used in data analysis. The instrument was essays test. The research conclusions were as follows; Firstly, Story map technique was better than cooperative learning STAD. Secondly, Story map technique improved the students’ writing ability in the aspect of content. Thirdly, Story map technique improved the students’ writing ability in the aspect of identifying organization, Fourthly, Story map technique did not improved the students’ writing ability in the aspect of vocabulary. Fifthly, Story map technique improved the students’ writing ability in the aspect of identifying language use. And the last Story map technique improved the students’ writing ability in the aspect of mechanics. For further researchers, it is suggested to carry out a similar research on conducting the study in a longer time because it will give a bigger significant effect to the students’ writing ability.